The Effect of Athletic Identity and Other Factors on Adaptation to Sport Retirement - Cota Powell, Andrea; Berg-Poppe, Patti; Pickett, Andrew C.; Ikiugu, Moses; Lucas Molitor, Whitney (Journal of Intercollegiate Sport, 2024)
Sport retirement is a major life transition that student-athletes must navigate successfully to achieve adaptation to post-sport life. Numerous factors dictate the likelihood of successful adaptation, one of which is athletic identity. Based on thorough review of the occupational retirement literature, it has been determined that adaptation can be measured by life satisfaction. Therefore, the purpose of this study was to determine how athletic identity impacts present-day life satisfaction and if meaning in life mediates that effect. Meaning in life can be separated into two categories, the presence of and search for meaning in life. Through a quantitative survey of 104 former Division I student-athletes, we discovered significant relationships between the search for and presence of meaning in life and life satisfaction. No relationship was found between athletic identity and life satisfaction. Thus, retrospective athletic identity does not predict present-day life satisfaction unless the mediating effect of the search for meaning in life is present. Additionally, group differences were measured between sexes, type of sport played (e.g., draft eligible or non-draft eligible), and predictability of retirement. There were significant differences on the Athletic Identity Measurement Scale between males (M = 36.1, SD = 7.9) and females (M = 32.1, SD = 7.8), t(100) = 2.55, p = .01.